Validasi Psikometrik Instrumen Digital Preferensi Sensori untuk Deteksi Gaya Belajar Matematika Siswa Sekolah Menengah - Santika, Satya; Nugraha, Depi Ardian; Mansyur, Muhamad Zulfikar; Marsika, Refi Dwi; Hendarman, Sherly Agustina (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
The urgency to individualize mathematics instruction in secondary education has highlighted the necessity for reliable, contextually appropriate assessment tools that identify students’ sensory learning preferences. However, existing instruments—especially digital ones—often lack rigorous psychometric validation, limiting their practical and theoretical utility. This study aimed to develop and validate a digital instrument for assessing sensory learning preferences (visual, auditory, kinesthetic) among Indonesian middle school students, focusing on content validity, construct validity, internal consistency, and item discrimination. Employing a research and development approach using the ADDIE model, the instrument was created through a participatory process involving experts in mathematics, educational psychology, and digital learning, alongside teachers and students. Validation processes included expert content review, pilot testing, and large-scale field implementation with 134 students from diverse urban and peri-urban schools in Tasikmalaya. Content validity indices indicated high expert agreement, while exploratory and confirmatory factor analyses confirmed a robust three-factor structure consistent with theoretical expectations. Reliability analysis revealed strong internal consistency across all dimensions. All items demonstrated satisfactory discrimination power. The digital instrument was positively received by both teachers and students, facilitating efficient identification of students’ dominant learning preferences and supporting adaptive mathematics instruction. This research provides empirical evidence for the feasibility and utility of psychometrically validated digital assessment in Indonesian educational settings, offering a scalable tool to promote data-driven instructional differentiation. Future studies are recommended to further expand the instrument’s scope and examine its impact on learning outcomes longitudinally.Keywords:          sensory learning preferences; digital assessment; psychometric validation; mathematics education; secondary school.